A ambientalização da formação do arquiteto : o caso do Curso de Arquitetura e Urbanismo da Escola de Engenharia de São Carlos (CAU, EESC-USP) - Pavesi, Alessandra (2007)
This research focused on the process of greening undergraduate curricula. It aimed to construct a theoretical and methodological procedure to investigate the components of such processes. The procedure used is based on an interpretation of the epistemological positions of a group of teachers responsible for the Architecture and Urbanism course of the Engineering School of São Carlos (EESC-USP, SP, Brazil): their values, experiences and practices, and the problems they have encountered in including environmental subjects in the curriculum. Within the wider debate on the greening of higher education, whose repercussions are manifested in Brazilian policies as well as academic discourse and research, the present analysis of the participating teachers concepts was based on writings by specialists in educating architects and constructing optimized curricula. The results reveal the complex, problematic nature of greening curricula, a process requiring more than the inclusion of environmental themes and content. Decisions and initiatives profoundly affecting curricula will also be necessary, entailing changes in their structuring and content organization and, therefore, in the dynamics of educational institutions, the courses offered by them, and the social web of which they are a part.